The introduction of leucotomy in Germany: National Socialism, émigrés, a divided Germany and the development of neurosurgery. Issue 3 (September 2019) - Rzesnitzek, Lara
Thinking about the chronology of the introduction of leucotomy in Germany sheds new light on the hypothesis of a special 'radical' approach of German psychiatry to the treatment of the mentally ill during the period of National Socialism. Moreover, it offers new insights into the transnational and interdisciplinary conditions of the introduction of leucotomy in early divided post-war Germany.